CoII Complexes as Liposomal CEST Agents. (18th May 2020) - Abozeid, Samira M.; Asik, Didar; Sokolow, Gregory E.; Lovell, Jonathan F.; Nazarenko, Alexander Y.; Morrow, Janet R.
Abstract: Three paramagnetic Co II macrocyclic complexes containing 2‐hydroxypropyl pendant groups, 1, 1′, 1′′, 1′′′‐(1, 4, 8, 11‐tetraazacyclotetradecane‐1, 4, 8, 11‐tetrayl)tetrakis‐ (propan‐2‐ol) ([Co(L1)] 2+, 1, 1′‐(4, 11‐dibenzyl‐1, 4, 8, 11‐tetraazacyclotetradecane‐1, 8‐diyl)bis(propan‐2‐ol) ([Co(L2)] 2+ ), and 1, 1′‐(4, 11‐dibenzyl‐1, 4, 8, 11‐tetraazacyclotetradecane‐1, 8‐diyl)bis(octadecan‐2‐ol) ([Co(L3)] 2+ ) were synthesized to prepare transition metal liposomal chemical exchange saturation transfer (lipoCEST) agents. In solution, ([Co(L1)] 2+ ) forms two isomers as shown by 1 H NMR spectroscopy. X‐ray crystallographic studies show one isomer with 1, 8‐pendants in cis ‐configuration and a second isomer with 1, 4‐pendants in trans ‐configuration. The [Co(L2)] 2+ complex has 1, 8‐pendants in a cis ‐configuration. Remarkably, the paramagnetic‐induced shift of water 1 H NMR resonances in the presence of the [Co(L1)] 2+ complex is as large as that observed for one of the most effective Ln III water proton shift agents. Incorporation of [Co(L1)] 2+ into the liposome aqueous core, followed by dialysis against a solution of 300 mOsm L −1 produces a CEST peak at 3.5 ppm. Incorporation of the amphiphilic [Co(L3)] 2+ complex into the liposome bilayer produces a more highly shifted CEST peak at −13 ppm. Taken together, these data demonstrate the feasibility of preparing Co II lipoCEST agents. Abstract : Paramagnetic Co II complexes produce water 1 H shifts that rival those of lanthanide(III) complexes. Incorporation of these complexes into the interior and bilayer of shrunken liposomes gives highly shifted intraliposomal water protons for chemical exchange saturation transfer (CEST) experiments as the first examples of transition metal ion lipoCEST agents.